2017
DOI: 10.3390/rs10010052
|View full text |Cite
|
Sign up to set email alerts
|

Effective Fusion of Multi-Modal Remote Sensing Data in a Fully Convolutional Network for Semantic Labeling

Abstract: Abstract:In recent years, Fully Convolutional Networks (FCN) have led to a great improvement of semantic labeling for various applications including multi-modal remote sensing data. Although different fusion strategies have been reported for multi-modal data, there is no in-depth study of the reasons of performance limits. For example, it is unclear, why an early fusion of multi-modal data in FCN does not lead to a satisfying result. In this paper, we investigate the contribution of individual layers inside FC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Recently, some studies [63][64][65][66] found that the effective fusion of color imagery with elevation (such as DSM) might be helpful to resolving these problems. The elevation data containing the height information of the ground surface make it easy to discriminate the building roofs from impervious surfaces.…”
Section: Limitations Of Deep Learning Models In This Studymentioning
confidence: 99%
“…Recently, some studies [63][64][65][66] found that the effective fusion of color imagery with elevation (such as DSM) might be helpful to resolving these problems. The elevation data containing the height information of the ground surface make it easy to discriminate the building roofs from impervious surfaces.…”
Section: Limitations Of Deep Learning Models In This Studymentioning
confidence: 99%
“…While the observational-level fusion directly combines raw datasets, the feature-level fusion integrates the feature sets derived from multimodal into a single feature set. Several researchers demonstrated the improved performance by multimodality fusion approaches [13][14][15]27]. However, the performance varies depends upon the robustness of fusion strategies and its efficacy to combine multimodal information in a more complimentary manner.…”
Section: Methodology and Conceptual Frameworkmentioning
confidence: 99%
“…In order to address this fundamental query, this research focuses on the 3D point cloud segmentation with various fusion and non-fusion approaches and evaluated the performance. If the data representation similar or transformed into a similar representation as in the case of [10,13], multimodality fusion can be carried out in numerous ways. Nonetheless, both data representation and range of values are different in LiDAR point cloud and images, and hence, the fusion approach has to respect the characteristics of both modality.…”
Section: Methodology and Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The image size normalization means to use a series of geometrical size adjustment to ensure that the original images have the unified size or location feature. In the course of image feature extraction, training or classification, a lot of images may be used, and the size normalization for image can ensure that the images processed have the same geometric feature, so as to ensure that the subsequent feature extraction or training can be smoothly carried out [3]. The image size normalization mainly includes scaling, translation and rotation.…”
Section: Digital Image Processing Methodsmentioning
confidence: 99%